Economic Synergy and Religious Tolerance in Tourism Villages: A Maqashid al-Shari’ah Perspective - Kholis Firmansyah; Raha Bistara (Journal of Indonesian Islamic Studies, 2026)
Intolerant attitudes may trigger interreligious conflicts in Indonesia. Therefore, there is a need for village-based public spaces that can simultaneously promote social harmony and strengthen the local economy. One such strategic public space is the Tourism Village. This study aims to analyze the role of Tourism Villages as spaces for economic synergy and religious tolerance from the perspectives of legal literature and maqashid sharia. This study employed a qualitative method using a library research approach. Primary data sources included laws and regulations concerning Tourism Villages, tourism, and religious tolerance in Indonesia, as well as Islamic legal sources such as the Qur’an, Hadith, and literature on maqashid sharia. Secondary data were obtained from academic books and scientific journal articles. Data were collected through documentation techniques and analyzed using content analysis with a normative legal and maqashid sharia approach. The findings reveal that Tourism Villages possess significant potential to strengthen the local economy while fostering interreligious tolerance. The principles of kinship, equality, local wisdom, and diversity embedded in Indonesian tourism regulations provide a strong foundation for developing Tourism Villages grounded in religious moderation. These principles are also aligned with the objectives of maqashid sharia, particularly the protection of religion (hifz al-din), wealth (hifz al-mal), and human life (hifz al-nafs).